2017
DOI: 10.1007/s10653-017-9995-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of biosolid hydrochar on toxicity to earthworms and brine shrimp

Abstract: The hydrothermal carbonization of sewage sludge has been studied as an alternative technique for the conversion of sewage sludge into value-added products, such as soil amendments. We tested the toxicity of biosolid hydrochar (Sewchar) to earthworms. Additionally, the toxicity of Sewchar process water filtrate with and without pH adjustment was assessed, using brine shrimps as a model organism. For a Sewchar application of 40 Mg ha, the earthworms significantly preferred the side of the vessel with the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…So far, only one study has conducted a limited ecotoxicological assessment. With the application of biosolids-derived hydrochar (190 °C for 4 h) up to 80 Mg/ha or 4 wt%, no acute toxicity to earthworms was identified, although earthworms showed significant preference to control soil rather than hydrochar amended (Melo et al, 2017). Limited reports have shown that using MS-derived hydrochar may pose environmental and human health risks but probably depending on the hydrochar properties, soil properties, and soil biota.…”
Section: Agricultural Applicationsmentioning
confidence: 99%
“…So far, only one study has conducted a limited ecotoxicological assessment. With the application of biosolids-derived hydrochar (190 °C for 4 h) up to 80 Mg/ha or 4 wt%, no acute toxicity to earthworms was identified, although earthworms showed significant preference to control soil rather than hydrochar amended (Melo et al, 2017). Limited reports have shown that using MS-derived hydrochar may pose environmental and human health risks but probably depending on the hydrochar properties, soil properties, and soil biota.…”
Section: Agricultural Applicationsmentioning
confidence: 99%
“…Previous studies to assess the toxic effect of hydrochar have focused on experiments with plants, in particular, evaluating the germination processes (Bargmann et al 2013;Fang et al 2015) and growth (Rillig et al 2010;Reibe et al 2015) as well as study the changes caused in the soil biota by hydrochar (George et al 2012;Salem et al 2013;Melo et al 2017c). Process water recirculation in the new HTC process has been reported in the literature as its main use (Lu et al 2014;Weiner et al 2014;Kabadayi Catalkopru et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Process water recirculation in the new HTC process has been reported in the literature as its main use (Lu et al 2014;Weiner et al 2014;Kabadayi Catalkopru et al 2017). However, the process water also has been evaluated as a culture medium for algal growth (Biller et al 2012;Hognon et al 2015), in seed germination studies (Bargmann et al 2013;Vozhdayev et al 2015), and recently using Artemia salina to assess its toxic effects (Melo et al 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, volatile compounds such as these may be associated with phytotoxic effects (Bargmann et al, 2013;Melo et al, 2017). There is no statistically significant difference in the relative germination number between the three conditions tested in the growth trials-all three hydrochar conditions do not affect the number of cress seeds germinating.…”
Section: Discussionmentioning
confidence: 95%